Fatigue study on the sensor performance of macro fiber composite (MFC): Theoretical and experimental approach. (15th August 2017) - Pandey, Akash; Arockiarajan, A.
Abstract: Due to its high flexibility and enhanced electro-mechanical coupling, macro fiber composite (MFC) is widely used in the area of sensing, vibration control and structural control. While in application, MFCs are subjected to continuous cyclic mechanical load which may lead to the deterioration of piezoelectric coupling coefficient, thereby affecting its sensing performance. In order to predict the life cycle of MFC ( d 31 & d 31 type) subjected to mechanical loading, an experimental setup has been devised and the tests are carried out for various loading conditions. For lowering the effort and cost involved in the experiments, a non-linear finite element model along with cumulative damage theory is introduced. The degradation in the piezoelectric coupling coefficient obtained using the current theoretical model are in good comparison with the experimental observations. The current non-linear FE model is also extended to predict the stiffnesses and strengths of the MFC as a function of fatigue cycles.